How Do Emotions and Feelings Regulate Physical Activity? - Ralf Brand (Frontiers Research Topics, 2017)
Up to date the scientific discussion about how frequency and regularity of physical activity can be increased is dominated by social-cognitive models. However, increasing evidence suggests that emotions and feelings have greater influence on physical activity than originally assumed (Rhodes, Fiala, & Conner, 2009). Generally speaking, humans possess an evaluative system with a basic action tendency to approach pleasurable events and to avoid aversive ones (Cacioppo & Berntson, 1999). Evaluative responses to a behavior and associated emotional states may influence a decision regarding whether or not to repeat being physically active. Generally, behavior associated with positive evaluations has a higher probability of being repeated than behaviors without such an association. On the contrary, an association with negative evaluations tends to decrease the probability of repeating to be physically active. Hence, evaluative responses to physical activity or the related situation can be an important aspect in the process of physical activity maintenance (McAuley et al., 2007). Several social-cognitive models of behavior change and maintenance were recently extended to take the influence of affective responses into account, in a way that variables already included in the models (e.g. outcome expectancies or attitudes) were more clearly articulated into their cognitive and affective components. For example, with regard to Social Cognitive Theory, Gellert, Ziegelmann and Schwarzer (2012) proposed to distinguish between affective and health-related outcome expectancies, and in the Theory of Planned Behavior, researchers suggested to differentiate between cognitive and affective attitudes (Lawton, Conner, & McEachan, 2009). The results of these and other studies suggest that affective components make a unique contribution to the explanation of the physical activity behavior (Brand, 2006). Other examples come from social cognition research, where it was shown that automatic evaluative responses are part of our everyday life and that they decisively influence health behavior (Hofmann, Friese, & Wiers, 2008). Accordingly, there is evidence that people who exercise regulary hold more positive automatic evaluations with exercise than non-exercisers (Bluemke, Brand, Schweizer, & Kahlert, 2010). Although significant progress has been made in showing that evaluative responses to physical activity and associated emotional states are important predictors of physical activity underlying psychological processes are far from being fully understood. Some important issues still remain to be resolved. Which role play affective states compared to concrete emotions when influencing physical activity? How do affective states and emotions interact with cognitive variables such as intentions? Are evaluative processes before, during or after physical activity important to predict future physical activity? Do negative and positive evaluations interact antagonistically or rather synergistically when physical activity as a new behavior shall be adopted? Future research will help us to resolve these and a lot of other so far unresolved issues.